Technology, market regulations, and labor share dynamics - Mary O'Mahony; Michela Vecchi; Francesco Venturini (Asian Development Bank Institute (ADBI), 2018)
We investigate the causes of the decline in the labor share, exploring the effect of technology vis-à-vis the role of market regulations, namely employment protection legislation, product market regulation, and intellectual property rights (IPR) protection. Our results show that, in the long run, productivity upgrades and information and communication technology capital diffusion are major sources of the decline in the labor share. IPR protection is the only dimension of the institutional setting that affects (positively) the share of industry income accruing to labor. Our results also show that hysteresis characterizes the dynamics of the labor share in all countries. This further corroborates the idea that institutional differences are not the main source of variation in labor share movements, as the negative trend is common to countries with different regulatory settings.
Keywords: C23; E24; E25; O33; 330; labor share; technological change; ICT capital; market regulations; hysteresis